On Weak Essential Ideals of Semiring - Pawar, Kishor Fakira (Communications in Mathematics and Applications, 2015)
In this paper we investigate a class of ideals that lies between essential ideals and semi-essential ideals, we call these class of ideals as weak essential ideals.